A mobile app-based intervention improves anthropometry, body composition and fitness, regardless of previous active-inactive status: a randomized controlled trial - Gómez-Cuesta, Nerea; Mateo-Orcajada, Adrián; Meroño, Lourdes; Abenza-Cano, Lucía; Vaquero-Cristóbal, Raquel (Frontiers in Public Health, 2024)
Introduction: The use of mobile apps to promote physical activity in adolescents can improve health-related parameters. However, previous studies have not evaluated whether the benefits depend on the users' prior active or inactive status. Therefore, the main objective was to analyze differences in physical activity levels, adherence to the Mediterranean diet (AMD), anthropometry, body composition, and physical fitness between active and inactive adolescents. Methods: The study was conducted through a randomized controlled trial (RCT) with 462 adolescents, divided into experimental (EG) and control groups (CG), further categorized as active and inactive. Variables of physical activity, kinanthropometry, body composition, and physical fitness were measured before (pre-test) and after (post-test) a 10-week intervention using step-tracking apps (Strava, Pacer, MapMyWalk, and PokémonGo) at least three times per week. Results: the results showed that inactive EG adolescents significantly increased their physical activity levels, body mass, and muscle mass, and improved in all fitness variables except the countermovement jump (CMJ). The sum of three skinfolds also significantly decreased. Active EG adolescents increased body and muscle mass and improved in all fitness variables. Additionally, they significantly reduced fat mass and the sum of three skinfolds. All covariates, mainly gender and maturity, had significant effects on the study variables. Comparing changes between the active EG and CG groups, significant differences were found in body mass index (BMI) and CMJ in favor of the EG. However, while significant differences were observed in the study variables when analyzing each app individually, there were no differences between the changes produced by each app in these variables. Conclusion: after a 10-week program of physical activity promoted through step-tracking apps, improvements were observed in fat variables, cardiorespiratory fitness, and curl-up performance. Furthermore, only inactive adolescents perceived an increase in their level of physical activity. The measurement protocol was registered prior to the start of the intervention at ClinicalTrials.gov (code: NCT04860128).